Crime suspenstories (1950), volume 4 ebook Crime suspenstories volume 4. - Various (Crime SuspenStories (1950), 2019)
Science Fantasy tales of a weird nature! This classic volume collects issues #19-22 of the groundbreaking comics anthology Weird Fantasy, as well as #25 and 26 of Weird Science-Fantasy-- fully remastered in digital color! Featuring strange and exciting tales from iconic writers and artists including Al Feldstein, Jack Kamen, Wally Wood, Jack Kamen, Joe Orlando, Al Williamson, and more!